Electron-beam induced damage process for Ca2Na2Nb5O16 nanosheets. (6th August 2022) - Choi, Haneul; Lee, Gwangyeob; Roh, Jong Wook; Park, Jin-Woo; Chang, Hye Jung
Abstract: Dielectric two-dimensional oxide nanosheets are attractive because of their thermal stability and high-k property. However, their atomic structure characterization has been limited since they are easily degraded by electron-beams. This study aimed to investigate the electron-beam induced damage mechanisms for exfoliated Ca2 Na2 Nb5 O16 (CNNO) nanosheets. Knock-on damage dominantly occurred at high voltages, leaving short-range order in the final amorphous structure. On the other hand, a series of chemical reactions predominantly occurred at low voltages, resulting in random elemental loss and a fully disordered amorphous structure. This radiolysis was facilitated by insulated CNNO nanosheets that contained a large number of dangling bonds after the chemical solution process. The radiolysis damage kinetics was faster than knock-on damage and induced more elemental loss. Based on our understanding of the electron beam-induced degradation, atomic-scale imaging of the CNNO nanosheets was successfully performed using Cs-corrected scanning transmission electron microscopy at 300 keV with a decreased beam current. This result is of particular significance because understanding of electron-beam damage in exfoliated and insulating 2D oxide sheets could improve identification of their atomic structure using electron microscopy techniques and lead to a practical guide for further extensive characterization of doped elements and layered structures to improve their properties.